PENGARUH AUGMENTED REALITY SENJATA DEWATA NAWA SANGA SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF TERHADAP PEMBELAJARAN AGAMA HINDU DI SD NEGERI 2 PERERENAN - Saskara, I Putu Adi (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2019)
Information and communication technology seems to have become a function of books, teachers and teaching systems that were previously conventional. The conventional learning system at this time makes communication between teachers and students less effective due to the lack of attention of students to the lessons explained by the teacher and students quickly saturated during the lesson. Based on the background of the problem, the researcher formulated a number of problem formulations namely 1) How to build an application that can facilitate students in learning and knowing the weapons of Dewata Nawa Sa??ga at SD Negeri 2 Pererenan, Pererenan, Mengwi, Badung? 2) What is the function of augmented reality weapons of Dewata Nawa Sa??ga as a communication media for Hindu religious education at SD Negeri 2 Pererenan, Pererenan, Mengwi, Badung? 3) How is the impact of augmented reality weapons of Dewata Nawa Sa??ga on learning Hinduism in SD Negeri 2 Pererenan, Pererenan, Mengwi Badung?The theory used in this study is structural-functional theory and persuasive communication theory. This type of analysis is research and development with the types of qualitative and quantitative data as supporters. To determine the informants in the field the author uses purposive sampling technique. Data collection methods used are observation, interviews, documentation and library studies.The results of the research obtained were the formation of an Android-based Augmented Reality Dewata Nama Sa??ga application. The function of this application as a learning media are: attention function, affective function, cognitive function, compensatory function, and motivating interests or actions, presenting information, and giving instructions. The impact is increasing student interest in learning, improving student learning outcomes with the percentage of 80.25% for the control class and 82.4% for the experimental class.